PSICOTERAPIA COM IDOSOS: UMA QUESTÃO PARA ALÉM DA CLÍNICA (REMUNOM, 2025)
This study has as its central theme psychotherapy aimed at the elderly, with an emphasis on the psychoanalytic approach, seeking to reflect on the place occupied by the elderly in contemporary psychological clinics. The choice of the theme is justified by the increasing invisibility and stigmatization that accompany human aging, often marked by reductionist views that associate old age with fragility, dysfunction and incapacity. Such a perspective contributes to the silencing of relevant subjective and psychosocial demands in old age. The research aims to answer the following question: How can psychotherapy, especially psychoanalysis, contribute to the promotion of the mental health of the elderly in a social scenario marked by stigma and invisibility? The general objective is to analyze the importance of psychotherapy in promoting the mental health of the elderly, highlighting the contributions of the psychoanalytic approach. The specific objectives are: (a) to identify the main challenges faced by the elderly in the field of mental health; (b) to reflect on the place of the elderly in contemporary psychoanalytic clinics; and (c) mapping actions that favor social and psychological inclusion in old age. This is a bibliographic research, with a qualitative approach, based on scientific articles published in the SciELO, PePSIC and Google Scholar databases. The selection criteria included productions in Portuguese, published between 2013 and 2023, that address mental health, aging, psychotherapy and psychoanalysis. The data analyzed demonstrate a significant lack of academic productions that focus on old age as a legitimate field of clinical listening, as well as a gap in the training and practice of mental health professionals in welcoming the singularities of the elderly subject. By highlighting this gap, the study contributes to broadening the debate on the urgency of a more inclusive, critical and sensitive clinical practice to the specificities of aging.